Design of Packed Column for C02 Absorption from NG at Reserves Using FLUENT - Abd Hamit, Haszlizah (Universiti Teknologi PETRONAS, 2010)
Nowadays, the high composition of CO2 at the gas reserves has incurred problem to the existing treatment system inthe gas processing plant. Assolution anadditional treatment plant can bebuilt at the gas reserves to reduce CO2 composition before the gas enters the processing plant. The option to use a packed column in this additional treatment plant is investigated. This dissertation explain the background, problem statement, objective, methodology and the finding of the modeling simulation present computational fluid dynamics model built in FLUENT in order to simulate the CO2 removal from high pressure natural gas using a specially designed solvent. The purpose for this simulation model is to study the behavior of mass diffusion of in the reactive absorption process with packing material as the contacting device in counter current absorption process. The packing area represent by a porous medium with 0.9 porosity. This research investigate the gas distribution throughout the column with 17ft packing height, at range of 1- 80 Bar operating pressure and the effect of liquid loading range from 50 - 150 mVm2h to the decrease ofC02 content. In the study involving gas distribution, height of the column also increase from 14ft to 17ft in order to observe the effect to packing area to the gas distribution..